Byron, Hunt, and the politics of literary engagement - Steier, Michael (New York : Routledge, 2019)
In the second decade of the nineteenth century, the British press began a campaign of critical abuse against Leigh Hunt, caricaturing the radical journalist as an upstart "Cockney" author whose literary talents were as disreputable as his politics. Lord Byron, on the other hand, was revered as a peer and a poetical genius who, the conservative press argued, would never befriend and collaborate with a writer like Hunt. Yet Byron did just that. Byron, Hunt, and the Politics of Literary Engagement is the first full-length study of the friendship and literary relationship of two of the most important second-generation Romantic authors. Challenging long-held critical attitudes, this study shows that Byron and Hunt engaged in a creative and meaningful dialogue at each major stage in their careers, from their earliest published volumes of juvenile poetry and verse satire to their most celebrated contributions to Romantic literature: The Story of Rimini and Don Juan. Drawing upon newly recovered letters and unpublished manuscript material, this book illuminates the surprisingly durable and artistically significant friendship of Lord Byron and Leigh Hunt.
OCLC-licensed vendor bibliographic record.
Keywords: Byron, George Gordon Byron, -- Baron, -- 1788-1824 -- Political and social views; Hunt, Leigh, -- 1784-1859 -- Political and social views; Politics and literature -- Great Britain -- History -- 19th century; Politics and literature -- Great Britain -- History -- 18th century; LITERARY COLLECTIONS / General; LITERARY CRITICISM / General